Avaliação do comprimento relativo do telômero em pacientes com lúpus eritematoso sistêmico e sua associação com características clínicas e cognição - Anna Carolina Faria Moreira Gomes Tavares (2023)
Introduction: telomeres are protein complexes located at the top of each arm of chromosomes, essential for maintaining the stability of the genome. Telomere shortening is found in physiological aging and senescence-related to systemic lupus erythematosus (SLE). Objective: to compare the relative telomere length (TL) in SLE patients and controls; to correlate TL of SLE patients with clinical outcomes, comorbidities, and treatments. Methods: cross-sectional study comparing patients with SLE and controls, aged 18 to 60 years, matched by sex and age. Clinical and demographic data were sex, age, education level, ethnic-race classification, comorbidities, anthropometric measures and relative TL, assessed by the real-time polymerase chain reaction (qPCR). This technique is based on determining the average cycle thresholds (Cts), which corresponds to the cycle number in which the fluorescence generated within a reaction exceeds the fluorescence threshold. The average Cts of telomeric DNA is normalized by the average Cts of the single-copy gene (36B4) in order to guarantee endogenous control of reactions. Additionally, for cases, we evaluated previous and current clinical manifestations and treatments, disease activity (SLEDAI-2K), damage (SLICC/ACR–DI), cognitive assessment (mini-mental state examination, fluency test, Schulman clock test, word list), fatigue (FACIT-Fatigue), depression, anxiety and stress (DASS21), and physical activity (IPAQ-SF). Comparisons of variables were performed using Student's t-test or Mann-Whitney test. Correlations were evaluated with Spearman's correlation coefficient. Characteristics with a p-value lower than 0.25 in the univariate analysis were included in the adjustment process of the initial multivariate model. Five multivariate models were performed. When more than one cognitive characteristic was present, they were included in the model separately, keeping the one with the lowest p-value in the initial model. Then, all the others were added, the stepwise backward method was applied and they were removed one by one until only those with statistical significance (p-value ≤ 0.05) remained in the final model. Finally, aiming to find alternative models, the exchange of the cognition characteristic that remained in the model for the others that left in stage I was tested; the inclusion one by one of all other variables with a p-value less than 0.25 in the univariate was also tested. The analyzes were made in the R version 3.6.3 and MINITAB programs. A significance level of 5% was considered. Results: Sixty SLE patients and fifty-five controls were included. Among patients, 75% were diagnosed with SLE in adulthood, 25% diagnosed in childhood; 86.7% were female (average age 37 years); 15% had antiphospholipid syndrome (APS), 51.7% had a previous history of nephritis and 23.3% had neuropsychiatric involvement. Among controls, 87.3% were female (mean age 38 years). There was no difference between the groups regarding gender (p=0.924) and age (p=0.737). Patients with SLE had significantly lower TL than controls, with a median TL of 0.80 and 1.07, respectively (p=0.005). By the multiple regression model (R2=18.4%), patients with APS had longer telomeres when compared to patients without APS (p=0.007). On the other hand, patients with moderate anxiety symptoms had lower TL (p=0.015) when compared to patients without or with mild anxiety symptoms. There was no association with disease activity or damage. Conclusions: this study showed that patients with SLE have shorter telomeres than controls, as evidenced in previous studies, as well as patients with SLE and moderate symptoms of anxiety, an association already described in other populations. There are no data in the literature that corroborate the finding of longer telomeres in patients with SLE and APS, which requires future studies to elucidate this association. Longitudinal studies are essential to evaluate the clinical implications related to TL.